Pathophysiology - Altered Physiological States 2018
DOI: 10.5772/intechopen.70598
|View full text |Cite
|
Sign up to set email alerts
|

The Way from Renal Calcifications and Urinary Crystals to Kidney Stones: An Important Aspect in the Pathogenesis of Calcium Nephrolithiasis

Abstract: The formation of calcium (Ca) stones occurs in an initial phase by fixed growth on kidney calcifications consisting either of intratubular crystal accumulations protruding in renal calices (Randall's plugs) or of interstitial hydroxyapatite deposits (Randall's plaques) broken through the covering epithelial layers. Crystal aggregation (AGN) seems to be responsible for stone growth during crystalluria. This chapter reports on new aspects of the AGN of calcium oxalate being the most frequent stone compound and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In recurrent stone formers CaOx and CaP nucleation can take place at the end of the descending limb of the loop of Henle [15, 29]. However, in most patients CaOx crystallization seems to start at the end of the collecting ducts where urinary passage is only in the order of few seconds [10]. Urinary transit time (UT) through the renal pelvic system on the other hand endures several minutes and is essentially influenced by diuresis.…”
Section: Theoretical Bases To Understand Calcium Oxalate Crystallimentioning
confidence: 99%
See 2 more Smart Citations
“…In recurrent stone formers CaOx and CaP nucleation can take place at the end of the descending limb of the loop of Henle [15, 29]. However, in most patients CaOx crystallization seems to start at the end of the collecting ducts where urinary passage is only in the order of few seconds [10]. Urinary transit time (UT) through the renal pelvic system on the other hand endures several minutes and is essentially influenced by diuresis.…”
Section: Theoretical Bases To Understand Calcium Oxalate Crystallimentioning
confidence: 99%
“…Eleven proteins are thought to be relevant for stone formation [9]. Measurement of crystal growth showed that the growth of CaOx is too slow to allow particles within the short urinary transit time through the kidney to be able to reach dimensions being big enough to be retained in the narrow renal tubular system [10]. However freshly formed crystals by aggregation (AGN) tend to form big conglomerates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation